PHENOMENOLOGICAL MODELING OF SOUND FIELD GENERATED BY TRANSVERSAL VIBRATIONS OF STRAIT-LINED AND CYLINDRICAL SOURCES - COSMA, Ioan; POPESCU, Diana Ioana (Studia Universitatis Babeș-Bolyai Physica, 2015)
The paper presents two physical models meant to calculate the characteristics of noise fields produced by real strait-lined sources. Our study highlights the complexity of phenomenological and mathematical correlations between the parameters that should depict the field of traveling waves generated by real cylindrical surfaces. Acoustically, the distribution of sound flows is modeled through beady vibrating string or cylindrical-tube sources. Our results, in conjunction with sound level sonometric measurements, permit many comparative analysis of effective perturbation in sound propagation. Together with point or spherical models, our results can be implemented in the training of future specialists in applied acoustics of environmental ecology.